(untitled) (Journal of Comparative & International Higher Education, 2023)
This research explores the employability of Chinese international graduates in the Australian labor market. It captures the significance of six forms of capital (i.e., human, social, cultural, psychological, identity, and agentic) to Chinese international graduates when they develop their careers in Australia. The research employed Bourdieu’s theory of practice and a capitals-based approach as the theoretical framework. Data were collected via an online survey (N=203) and in-depth interviews (N=14). The findings reveal that in addition to getting employments in Australia, the graduates also benefited from developing and utilizing these six capitals in terms of sustainable employments, professional growth, and well-being. As such, this research argued for a broad definition of employability which include different capitals as the inputs and different aspects of employability outcomes as the outputs, namely, employment outcomes, sustainable employments, professional growth, and well-being. The findings also implied that various stakeholders should share responsibilities to support international students in building multiple capitals.